A New Stable, Explicit, Third‐Order Method for Diffusion‐Type Problems. Issue 6 (25th March 2022) - Kovács, Endre; Nagy, Ádám; Saleh, Mahmoud
Abstract: This paper reports on a novel explicit numerical method for the spatially discretized diffusion or heat equation. After discretizing the space variables as in conventional finite difference methods, this method does not use a finite difference approximation for the time derivatives, it instead combines constant‐neighbor and linear‐neighbor approximations, which decouple the ordinary differential equations, thus they can be solved analytically. In the obtained three‐stage method, the time step size appears in exponential form with negative coefficients in the final expression. This property guarantees unconditional stability, as it is shown using von Neumann stability analysis. It is also proved that the convergence of the method is third order in the time step size. After verification, by solving Fisher's and Huxley's equations, it is demonstrated that it works for nonlinear equations as well. The new algorithm is tested against widely used numerical solvers for cases where the media is strongly inhomogeneous. According to the results, the new method is significantly more effective than the traditional explicit or implicit methods, especially for extremely large stiff systems. It is believed that this new method is unique in the sense that it is the first unconditionally stable explicit method with third‐order convergence. Abstract : In this article, Kovács, Nagy, and Saleh propose a novel explicit, stable, third‐order numerical method for the diffusion equation. The new algorithm is applied for the nonlinear Fisher's and Huxley's equations, then tested for heat conduction to show that it is more effective than the traditional explicit or implicit solvers, especially for extremely large stiff systems.